The economics of the enterprise for ASEAN initiative - Naya, Seiji; Plummer, Michael G. 1959-.; Institute of Southeast Asian Studies; Gale Group (Singapore Institute of Southeast Asian Studies, 2005)
"This is a substantial exploration of many aspects of the Enterprise for ASEAN Initiatives (EAI) as envisaged in 2002 by the Bush administration in the United States. Included are discussions of the nature of US-ASEAN trade relations."--GVRL description.
Chp. 1. Introduction and overview -- Chp. 2. Introduction to the U.S.-ASEAN economic relationship -- Chp. 3. Economics of U.S.-ASEAN free trade agreement -- Chp. 4. Special issues in the EAI bilateral FTAs -- Chp. 5. EAI in a dynamic policy context -- Chp. 6. The economic case for U.S.-ASEAN bilateral free trade areas.
Electronic reproduction.
Keywords: ASEAN; Free trade -- Southeast Asia; Free trade -- United States; Southeast Asia -- Economic integration; Electronic books; United States -- Foreign economic relations -- Southeast Asia; Southeast Asia -- Foreign economic relations -- United States